Communicative language teaching activities for the development of english speaking skills in 6th and 7th grade students at escuela particular el crisol - Morales Cerezo, Gladys Denisse (2018)
In our country, people learn English as a foreign language since the first years of school. This fact could be convenient to the appropriate development of the mastery of the new language. However, the fact of being immersed in the second language does not guarantee the ability to speak the target language, especially when learners are requested to participate in communicative activities. Many of them experience low self-esteem, nervous, lack of confidence, and fear when they want to share their ideas, opinions, feelings in the new language. As a result, people do not develop their speaking skills adequately during foreign language classes. For that, some researchers consider that these problems present in learners are due to the lack of knowledge in the teaching and learning of the English language and its respective language skills. The main objective of this investigation project is focused on the development of speaking skills to enhance performance in the English classes through Communicative Language Teaching Activities (CLT) in 6th and 7th grade students at Escuela Particular “El Crisol”. This trouble is affecting in the learning of a second language to students. As a consequence, this limits the development of speaking skill………..